Промышленная проверка работы гидроциклона - Никитин, Н. И.; Шапорев, Валерий Павлович (НТУ "ХПИ", 2006)
У статті надаються порівняльні дані промислових випробувань роботи гідроциклона НТУ "ХПІ" і гідроциклонного устаткування фірми PARNABY (Англія). Технологічні дані класифікації вугілля у гідроциклоні й на гідроциклонній установці PARNABY показали перевагу першого та доцільність використання апарату НТУ "ХПІ" у промисловості.

The article gives comparative data on industrial testing of NTU "KhPI" hydrocyclone performance and of the hydrocyclone equipment produced by the PARNABY company (England). The technological categorization data of coal in the hydrocyclone and in the PARNABY hydrocyclone installation have shown the advantage of the former and the practicability of using the NTU "HPI" device in industry.
Keywords: обогатительная фабрика; ОФ; суспензия; классификация углей; гидроциклонная установка